CODESRIA Bulletin Online, No. 12, August 2022 - (In)Validating Crises in African Studies: Certain Reflections on Disciplinary Stagnancy - Odanga, K. René (CODESRIA Bulletin, 2022)
We are forced to deal with the words of that Franco-German singular genius, the author, missionary, musician, philanthropist, philosopher and physician, Dr Albert Schweitzer. ‘The African is indeed my brother, but he is my junior brother by several centuries.’[1] In 1931, he wrote his autobiography, Out of My Life and Thought, detailing his work in Africa as a medical missionary. Naturally, the book was an instant bestseller. And why would it not be? After all, in it he described how during his military service in his younger years, Jesus Christ—the very son of the Christian God—called him to ‘heal the sick, cleanse the lepers, raise the dead, cast out devils: freely ye have received, freely give.’[2] (It should be noted that he chanced upon this verse while reading the Bible in Greek, for he was a linguist too!) And what had he received? Degrees from the Kaiser Wilhelm University of Strasbourg in Theology, Philology, and the Theory of Music. Afterwards, he would also receive a medical degree specialising in tropical medicine and surgery. A few years later, with his new bride in tow, he sailed off on Good Friday to what is present-day Gabon to open a hospital, where he was the paternalistic doctor. His wife would be the nurse as soon as she figured out the pesky art of how much anaesthesia to administer to his patients, which she eventually did (for whatever one says of the Schweitzer family, they were nothing if not autodidacts). When not treating Africans in Lambaréné of maladies that Howard Markel calls ‘horrific and deadly’—chief among them being leprosy, just as in the Bible whence he received his commission—Schweitzer was to be found carrying out exegeses of Pauline theology or writing on the religious thought of Immanuel Kant, for which he received a doctorate from the Sorbonne. Alternatively, he was designing and playing pipe organs and pianos and contributing to music theory, specialising in the repertoire of Johann Sebastian Bach: in fact, one of the world’s foremost conductors of the compositions of Bach, Hans Münch (no, not the Nazi doctor, another one), studied under Schweitzer. Or he was touring the world in the company of Albert Einstein (and playing the violin with him), Otto Hahn and Bertrand Russell, all of them presenting lectures on the dangers of nuclear proliferation and the atom bomb to tune the scarred consciences of those who after World War II deplored the events in Hiroshima and Nagasaki. His philosophy was built on and named, ‘Reverence for Life.’[3] For his troubles, he was awarded the Nobel Peace Prize in 1952. Albert Schweitzer—that polymath, a true scholarly genius and earnest humanist. Let us find another word he offered about the Africans to whom he devoted so much of his life. Speaking of the orange trees planted in his hospital at Lambaréné, he said, ‘I let the Africans pick all the fruit they want. You see, the Good Lord has protected the trees. He made the Africans too lazy to pick them bare.’[4] The hospital he built in Gabon (with his own hands) and where he died, is named L’Hôpital Albert Schweitzer and is regarded by some as a pilgrimage site.[5] Whatever debates surround and pierce the field of African Studies, its history, methodology, epistemology, theory, economic viability within the academy and praxis, political or sociocultural utility, even disciplinarity, they all percolate around the same matter, the subject of study—the African. And while many scholars grapple with the question of the origin, scope, and methodology of the field, whether they know it or not, the question they are engaging with, is the African themself. Even the various epochs into which African Studies is periodised by scholars represent not just the ongoing politico-academic contexts and discourses of the day but, more significantly, the place of Africans and the evolution of the outlook towards them by the world: where ‘the world’ subsumes both the non-African academic and the African academic, the latter of whom is carrying out an exercise of self-study and reflection—whether they like it or not. As a student in African Studies, I have had the vantage to observe the field for myself in especial contexts over the past two years and to interrogate those contexts and the discipline as it relates to its ostensible subject: the African—myself. I have noted that African Studies is characterised as being in ‘perpetual crises’ pegged to the dominant discourses of the day. In fact, a not insignificant part of instruction at the graduate level entails training on how to navigate such ‘crises.’ My own qualifying examination, for instance, featured a mandatory long essay on the need for decolonial methodology in African Studies. This observation is in no way revelational; it is an open secret. And writing on the matter within the discipline has so proliferated that it has become a genre unto itself.[6] My concern, however, is that the process by which students and early career scholars are brought to this realisation constitutes an institutionalised form of scholastic hazing, which I will come back to later. My reflection on the discipline, its current state and possible future, arises from my time at Howard University’s Center and Department of African Studies and my interactions with colleagues at other institutions and fora. I want to choose my words carefully for the profit of clarity. For I have looked upon the scene and seen what I have seen. There is no crisis in African Studies. There never has been. There are no debates. No discourses. There is only white supremacist power maintaining its grip as a system and as the main arbiter of the African people and, by the transitive effect, the African reality. And as many well-meaning individuals and organisations fight to dislodge this power from its erstwhile throne, it reasserts itself through any number of wiles, generating and perpetuating ostensible crises.[7] The scholarly reflex to this has been to ‘debate’, ‘interrogate’, ‘discourse’ and ‘scholarly dialogue’ in a supposed search for solutions. This debate must now be rejected, the interrogation must be dispensed with, no such discourse should occur and all calls for dialogue must cease. For in truth, the germ of such dialogue, certainly what is at the heart of the question that would guide such discourse, is the most profane intellectual quibble with which humanity has ever been assaulted: the equality of the African. And that is assuming that what is to take place is by any definition of the term a ‘dialogue’. We shall return to the missioniser Schweitzer in due course, since for his (ir)relevance to be made manifest it is useful to present the operational structures that privilege labours such as his. While the man may not have considered himself an Africanist, surely there can be no doubt that he was preoccupied with the study of Africa. I am saying that were he miraculously alive today he would have had no challenge gaining affiliation to some organisation involved in the discipline; it would not be out of place to find him presented as keynote speaker for some African Studies association or other. Do I traffic in hypotheticals? Your indulgence. I And so there I was a few months ago, thoroughly horrified as I stared at an invitation to a webinar titled ‘Rethinking African Agency in Africa-China Relations’, received from any one of the numerous listservs to which I am subscribed. But the horror had arrived upon me slowly, as if it were some sort of realisation that dawned in its own time: the result of a subconscious connection of dots. I had begun to observe a pattern in the themes of fora that analysed African politics comparatively with any other country or region, particularly China. Comparative study routinely pitted Africa—a continent with fifty-four countries and upwards of a billion people of variegated cultures, thrust across disparate geographical zones and politico-economic realities—against a singular actor: ‘China-Africa, Brazil-Africa, India-Africa,’ et cetera. Even the concepts ‘US-Africa’, ‘UK-Africa’, ‘EU-Africa’ startle, save for an appreciation of the regions’ imperialist projects that prefer a monolith. And despite the general unseriousness that characteristically accompanies analyses of Sino-African relations, the source of my apprehension lay elsewhere.[8] It has become inevitable to see discussions redefining, searching for, or ‘rethinking’ African agency proliferate. Agency … that notion so ordinarily a capacity of humanness, that individuals can act and through these actions shape their realities. Not for Africans though, not for them and not for their governments, not for their diasporas either. African agency is a thing not taken for granted. It must be searched for then discovered; debated, defined, redefined, then rethought; edited and reviewed; in a way not done for any other peoples. And this has become a whole field of study! I am unable to see how all the pundits involved in this exercise have not yet conceived that the discussion they are engaged in is a question on whether the African is human at all. Agency. I would very well like to see that word expunged from all scholarly conversation until such time as it is not taken as a trait yet unfound in the African. Remarkably, while conversations on Africa question ‘agency’—or the lack thereof—the comparative actor is granted such aspects as power, interests, agenda and so on. ‘African Agency in the Face of Chinese Power’ was the title of another such webinar. II Some certain scholar recently landed in a pot whose roiling waters he himself had brought to boil for the purpose. When the furore broke, my immediate impulse was to ignore it hoping it was rightful comeuppance for a series of deliberate decisions taken by an individual in a position of power, as one makes one’s bed and so on. Then an intriguing thing began to occur before our very eyes, as outcries of support for said scholar from every corner of the world began to make themselves heard with striking resonance! It was harrowing. Watching university administrators, departmental heads, professors, supposed leading minds and thinkers, et cetera, trusted with nurturing and protecting students in such very universities, trip over themselves in the rush to defend one charged with endangering, to the vilest degree, those in their care.[9] It was obscene. Even before the fallout that will undoubtedly come and as many walk back their support and others doggedly maintain it, the spectacle offers the opportunity to reflect on certain realities brought out into the open. Of the rot it unveiled in ivory (and crimson) towers, much of it was known anyway, and power protecting power is academe’s modus operandi writ large. I shall stick to the tangential since the direct are matters that one hopes will be resolved in other quarters. The fealty displayed brought into sharp relief the massive meshwork that certain academics have created and control for their own means, thereby revealing their capacity to reproduce themselves throughout the fields they inhabit. Some colleagues, in lamenting his lot, showed their hand by witnessing that, ‘for five decades [he had] trained and advised hundreds of Ph.D. students of diverse backgrounds, who have subsequently become leaders in universities across the world.’[10] Elsewhere, he would be described as, ‘a renowned scholar and a gatekeeper in his field ...’ and ‘one of the world’s leading experts on Africa and the Global South.’[11] This liberal employ of superlatives did not concern me. I have no precise problem with institutional grandstanding—in fact, I intend to do some of my own shortly! I was more concerned with what it meant for the fields he inhabited that a potential shake-up in halls of power produced such a visceral reaction among the who’s who in academia. A statement was being made here that everything was fine and should be left as it was: a demand for stasis. If we accept that certain academics recreate their fields in their own image and likeness—and we must accept it since they admitted as much—then we must wonder as loudly as we can, what those disciplines look like and whether we are comfortable with that image; more importantly, why we would be comfortable with it. As the debacle continued, conversation quickly degenerated into whether our ‘leading expert on Africa and the Global South’ here could still be assigned as reading in classes. Some were conflicted to no end, and soon, hackneyed aphorisms about separating artists from their art (hence scholars from their scholarship) were polished and resubmitted for our collective edification. It was here that I had to confront a fundamental reality in my case: I had never heard of this man before this point. Two years into a graduate programme in African Studies at a university with a lengthy history of engaging ‘Africa and the Global South’, and he had never come up even in passing conversation until he burst upon the scene under questionable circumstances. And if insistence on his pre-eminence should have caused me to doubt the rigour of the department in which I was enrolled, that would have been uncalled for. You see, Howard University, being a Historically Black College and University (HBCU), maintains a different definition, persuasion, and tradition of ‘expertise’ on ‘the Global South’ in general and on Africa in particular. I contend here that the expertise that was so matter-of-factly imputed on this scholar was not necessarily a factor of the quality of his work—nor am I making a summary review of his work. I am zeroing in on the practice, so ordinarily an aspect of academia, that situates the ‘expert’ in certain towers. That practice is not a mistake. It is the result of a conscious, calculated, systemised, decades-long heist within the Western academy to privilege scholarship on Africa by Euro-Americans over that by Africans and African-descended scholars. The relegation of the role of HBCUs and African universities in the race for knowledge on Africa to trivia, is an ongoing project in African Studies; and the subsequent perpetuation of a canon that should not be displaced is an operationalisation of that system. Some trivia. By 1940, the Department of History at Howard University taught Ancient African Civilisations, Cultures and History, as the brainchild of William Leo Hansberry. Faculty within the university constituted, among others, the likes of Alain Locke, E. Franklin Frazier, Ralph Bunche, Rayford Logan, Merze Tate, and the later prime minister of Trinidad and Tobago, Dr Eric Williams, fresh from doctoral study in London and preparing the publication of his seminal work, Capitalism and Slavery. There were frequent campus cameos by W.E.B. Du Bois. Hansberry would mentor a young Ghanaian student from Lincoln University in Pennsylvania—another HBCU—and an athletic Nigerian on Howard University’s swim team: Kwame Nkrumah and Nnamdi Azikiwe. Over the years, the campus remained a crucial site of organisation, first on Ethiopia’s war against Italian aggression and later the anti-apartheid movement.[12] In 1959, a near-independent Kenya’s Tom Mboya made the university one of the first stops on his tour of the USA, where he was fêted with an honorary Doctor of Laws.[13] And the United States Supreme Court Justice, Thurgood Marshall, a graduate of both Howard and Lincoln, greatly assisted in the writing of Kenya’s independence Constitution.[14] (Meanwhile, a top-ranked African History programme in the USA has the following as its blurb: ‘African history is a new and dynamic field dating back to the 1960s. It was linked to the decolonization of Africa and the need for new national states to have a usable past.’[15] Whatever we are to do with the labours of Hansberry et al., we are not told. And if I were to bring up my grandfather born well before then, or his grandfather before him, and the histories they inhabited and made ‘usable’, I would complicate the matter even more and risk being christened the biased scholar incapable of objectivity. In this making of an African tabula rasa, this foul resurrection of Trevor-Roper, we are shown that white academia would rather plumb the depths of epistemicide than acknowledge the presence and value of Black scholarship.) Today, Howard University’s campus continues as a hub of research and training on Africa, maintaining a programme that enrols the largest number of African language students in the United States, instructing seven widely spoken languages.[16] Faculty with research interests on Africa are found in virtually every department plus a dedicated Department of African Studies. An anecdote. At a planning meeting for one of the many Africa-focused events that the Center for African Studies partners with organisations around Washington DC to host, it was suggested that panellists be sourced from Howard University faculty. One of the partners remarked bemusedly, ‘Oh, I didn’t know Howard did Africa like that!’ Of course. III I have mentioned a canon. Let me pursue it a bit further. After all, the matter has taken up some space lately in the academy generally and in African Studies particularly. At the recently concluded African Studies Association of Africa (ASAA2022) Conference in Cape Town, South Africa, the matter of subverting the colonial archive was front and centre in many sessions. I presented on a panel titled ‘Decolonising African Knowledges’ and attended around three sessions throughout the five-day conference on some form of ‘decolonising’ or other. Unfortunately, I could not identify with most of the crises that were under consideration given that I did not inhabit them. I have come to find these cyclical conversations on ‘decentring whiteness’ by theorising Blackness around whiteness and raising sterile questions on the horizon of liberation emblematic of an academic middle class that ‘speaks as if its identity or the crisis of its own identity is that of society as a whole.’[17] What is more, these unmoored conversations take place totally divorced from the long, rich histories of liberational praxis that African and African descended peoples have laboured for through time, so that they are always starting from scratch in a race for decolonial ‘originality’. I was unable to contend, for instance, with the matter of racist and paternalistic scholarship on Africa since my programme and advisers had not subjected me to such. I can hear it in my mind’s ear already, someone saying that this is a call for intellectual coddling. Far from it! It cannot be overstated that the decision to refuse to consistently platform infantilising scholarship on Africa is an intellectual act of resistance. The everlasting debate on what we are to do with Bruhl, Conrad, Hegel, Leakey, Livingstone, Lugard and so on, in truth, perpetuates them and the system that rewards them. This constant contest is the continuation of a structure of white supremacy that has kept serious Africans and African Studies scholars explaining and re-explaining themselves for far too long at the expense of valuable work. We are losing ground. ‘Who one reads,’ is as much a political question as it is an intellectual one—it always has been. ‘Who one is expected to read,’ even more so. I have recoiled in the past when colleagues enrolled in peer programmes shared with me their syllabus reading lists and on them was nothing but Naipaul, Conrad, Blixen and Huxley with token appearances by Achebe, Adichie and La Guma. I am not interested in the prose expertise of Naipaul. In fact, I am positively exhausted of hearing about it. To decide that his is an epitome of African literature—or ‘literature on Africa’—is a deliberate political choice. (On a similar note, it has become a matter of impish humour to discuss with my classmates and some professors the otherwise well-received works of scholars like Bayart and Ellis. We find them funny, in a dangerous sort of way.) But I want to ask what happens in the mind of the African student who is sat in a classroom and caused to analyse, discuss, debate Naipaul’s A Bend in the River on its merits as a masterful work of literature, as my colleague was caused to do and like many after him will be. The affliction is ongoing, we remain surrounded. I want to know what is done to the mind of the African scholars who are expected to engage with and respond to the most pedestrian of publications masquerading as scholarship with measured critique and debate, to pen rebuttals when the pivot on which such scholarship turns remains the sly questioning of the African’s humanity. Debates on ‘decolonisation’ in African Studies, couched in ‘good faith’, have become this: white scholars testing how much they can get away with and African scholars begging to be taken seriously. Such debate should cease. And what is with this insistence that we must engage with the conversation anyway? It is the misrepresentation of Euro-America’s monologue as dialogue. For it is difficult to show that Euro-American scholarship on Africa ever intended to speak with Africans about their Africa. Worse, that Africa should ever talk back.[18] This monologue has been cunningly disguised as a ‘crisis’. So now, we have been turned into perennial faultfinders, perpetual nit-pickers and, in some instances, ingrate interlopers. Before we can embark on our own work, we are inundated by that of others which purports to speak with even clearer voice. And we must ‘debate’ them. We must go through their profitless product with a fine-tooth comb, a process deliberately designed and ingeniously engineered to break both our picks and our backs, but disingenuously disguised as ‘scholarly discourse’. Ridiculous. Additionally, we are first forced to admit to the genius of paternalistic scholars. Whatever one may think of Schweitzer or Naipaul, or that academic in hot water, or any number of frontiering ethnographers or historians and so on, first, we must admit to and ingratiate ourselves with their genius: genius as a qualifier to indispensability. Rarely is the danger of their scholarship ever accepted as grounds for disqualification in being the arbiter of African life. Let us return to our good saint and medic Schweitzer, who viewed Africans as primitive children, who ‘scarcely ever talked with an adult African on adult terms.’[19] Has much of his image changed in view of his racist attitudes? I would say certainly not. After all, one most recent appraisal of his life is only able to call him ‘a figure of controversy and embarrassment’ even as he stood in the way of African decolonisation efforts.[20] And did we not see attitudes similar to his bring about great suffering? (The British colonial administration in Kenya from 1952 to 1961 worked with an unceasing fidelity to pseudo-psychiatric reports by physicians who shared Schweitzer’s outlook. In reading them, one clearly sees representations of Africans as Schweitzer’s ‘junior brothers’, primitive children. During that ten-year State of Emergency, countless African lives were lost. Even though he may not have trained these charlatans, his views on the world stage certainly did not help matters! This is to say that his contemporaries, whether writing up quack psychological reports for colonial overseers in African dominions or establishing racist departments and associations of African Studies in North America, certainly found in Schweitzer no obstacle to their white supremacist projects. How much of a visionary can one be if one cannot rise above the myopic racialism of the field they inhabit? Genius that cannot find its way around and against the obvious obstacles that litter the road. What a useless endowment! Does it appear that with one broad stroke I am calling for the abrogation of many works and schools of thought that have formed common wisdom in the study of Africa? Well, that is so. We must admit that in the Africanist kingdom the emperor has been found on multiple occasions in various states of déshabillé. Therefore, comrade, you will hold as enemies—loftily, lucidly, consistently—not only sadistic governors and greedy bankers, not only prefects who torture and colonists who flog, not only corrupt, check-licking politicians and subservient judges, but likewise and for the same reason, venomous journalists, goitrous academicians, wreathed in dollars and stupidity, ethnographers who go in for metaphysics, presumptuous Belgian theologians, chattering intellectuals born stinking out of the thigh of Nietzsche, the paternalists, the embracers, the corrupters, the back-slappers, the lovers of exoticism, the dividers, the agrarian sociologists, the hoodwinkers, the hoaxers, the hot-air artists, the humbugs and in general, all those who, performing their functions in the sordid division of labor for the defense of Western bourgeois society, try in diverse ways and by infamous diversions to split up the forces of Progress—even if it means denying the very possibility of Progress—all of them tools of capitalism, all of them, openly or secretly, supporters of plundering colonialism, all of them responsible, all hateful, all slave-traders, all henceforth answerable for the violence of revolutionary action. And sweep out all the obscurers, all the inventors of subterfuges, the charlatans and tricksters, the dealers in gobbledygook. And do not seek to know whether personally these gentlemen are in good or bad faith, whether personally they have good or bad intentions. Whether personally—that is, in the private conscience of Peter or Paul—they are or are not colonialists, because the essential thing is that their highly problematical subjective good faith is entirely irrelevant to the objective social implications of the evil work they perform as watchdogs of colonialism.[21] IV There endures within academia a great delusion that any thought, no matter how dastardly, can be balanced out by savvy responses and critique. That academics fight using their pens, and that, indeed, the pen is mightier than most swords. Academic outlets hence (colleges, conferences, journals, publishers, scholar associations, scholars themselves, et cetera) have seized upon this delusion-turned-norm to platform the harm that is dreamed up and made real by certain researchers while themselves maintaining faux-neutrality in all matters.[22] Unethical articles are to be published then responded to by ethical rejoinders, unsound racist arguments are to be countervailed by rational and reasonable riposte, works that trivialise and caricature African life … a most unappealing game of seesaw. All this is done in practice of academic freedom, the pursuit of building upon knowledge and that greatest hoax of all time, academic objectivity.[23] This ruse, when applied in the study of Africa, takes on an even more egregious form. It has refused to enter academia’s mind that in Africa and the rest of the imperialised world the pen is not necessarily mightier than the sword; rather, the pen is the forerunner of the sword. I am not talking about that scalpel-wielding American evangelical, nor am I talking about any number of military men running roughshod all over the continent and leaving destruction in their wake (although of course the murderous missionary and the marauding militiaman can both be said to be involved in their own sort of study of Africa.)[24] I am talking about the Pentecost-esque revival of primitive practices of study that are reaffirming themselves in disciplinary interaction with Africa, where scholarly objectivity somehow translates to turning the African into an object. A Better Last Word Consider some article published by ‘North America’s leading forum for African Studies scholarship.’[25] This paper, intending to advocate for the mainstreaming of a particular anthropological methodology in African Studies, brought great outcry from scholars in many fields. Certain anthropologists and historians themselves familiar with the esoteric vocabulary and praxis at play were scandalised and made their distaste known. Apparently, the paper had taken certain liberties that were bad practice and that, among other things, cast their profession in a bad light.[26] I am not an anthropologist, so this did not concern me. And I am still persuaded that Anthropology—that most irretrievably colonial of disciplines, in view of its history in Africa—remains a disciplinary rubbish heap. A(n) (in)discipline which, with all the friction it insists on stirring with its interlocutors, may very well one day spark a fire that will reduce the whole enterprise to ashes.[27] Come, thou sacred flame! Instead, I allied myself with others who saw the provocation differently. The matter at hand was not that the paper was badly written, weak in its argument or factually dubious (it was); it was that the thing was dangerous. And that it should not have been platformed by a journal insistent on its centrality in the study of Africa, especially since said journal had, only two years before, been publicly self-flagellating in declarations of its intent to combat the history of white supremacy within its own ranks.[28] We firmly believed that the article reduced the authors’ interlocutors to native informants while claiming that it was in fact decolonising the discipline. This was evident in the paper itself and in the repertoire of one of its authors. We knew what we were looking at, as did many others. We called on the journal to retract it.[29] We insisted that the editorial board take a retroactive stand that it would not platform works that reduced the essence of African life. We appealed to the journal’s own affiliation with an association that had over the years been at the centre of the ‘crises’ in African Studies and that had also subjected African Studies scholars to rite after rite of contrition and promises to de-platform white supremacy and the privileges flowing thenceforth that valorised mediocre scholarship on Africa.[30] Our call invited the journal to break with the academic delusion of opening up matters that should not be up for debate to the marketplace of argumentation in ‘special editions’ and ‘responses’. We made plain that a retraction was the only way forward since we were ‘not interested in having our humanity as scholars and research subjects debated.’[31] And neither was this a fringe position, our letter was opened up to concerned publics for support and within a week garnered over a thousand signatures, predominantly from (early career) academics and graduate students from all over (not just Euro-America). First, we were treated to incredulous prevarications designed to frustrate. Suddenly, we were in the presence of the artisanal, fastidious barber: splitter of hairs. Then, finally, the editorial board responded with all the unimpeachable wisdom of a colonial missionary school headmaster, insisting that not only was our outcry uncouth but it had also caused much grievance to the authors of one of the most offensive papers in recent memory to assault otherwise hapless audiences. Conflating our call for amends with threats of violence that they assured us had been levelled against the authors of the article, they insisted that our responsibility, instead, was to lead the charge in defending the authors from the unsubstantiated gathering mob.[32] Here is this: people’s feelings are not more important than the material inequalities and iniquities their tangible actions and skewed scholarship perpetrate against the imperialised of this earth. Somewhere in that article, one author speaks of their elusive search for a space to discuss their experience of being a white scholar, ‘an umuzungu’, in Black Studies. Their area of study is Rwandans living in Canada.[33] I have never been to Canada, and to Rwanda only once. I have lived in East Africa all my life save for two years spent studying in the United States. Perhaps Euro-Americans would take it from me with some authority that the word mzungu is not necessarily one they should want to embrace. But this is to digress. Was this paper really trying to present the idea that the only utility of Black intellectual production, of Black scholarship, of research, of presence, of community, of Black people, of Black life, is to convict the white investigator of their whiteness? How woefully boring! How unutterably uninteresting in every possible way! How most sufferingly shallow! Is this to occur still? And is it to be called a ‘new form of writing?’[34] What, we must ask, is ‘original’ about exploitative, extractive Western scholarship on Africa? What is new, in any sense of the word, about parochial approaches to writing about Africa that valorise the heroic ambition of the ‘scholar’ while downplaying, yea even erasing, the life of Africans, relegating them to native informants? Is this not the most banal, boring, common, derivative, imitative, most readily available work? Surely this tradition dates back hundreds of years! Is any scholar who intends to peddle in such drivel really going to claim to be original or evocative? What avaricious new vistas of paternalism would they intend to chart then? We must forestall them! Here too is this, the Euro-American scholar of Africa ‘must cultivate the habit of humility appropriate to his limited experience of the African world and purged of the superiority and arrogance which history so insidiously makes him heir to.’[35] And neither should we be deterred by podiums that consider the position that African life is no longer debatable ‘ill advised’. Outlets that respond to a call for amends with such imperious finality as, ‘We decline to do this. We cannot do this. We fail to see how…’ must no longer be upheld as mediators of serious intellectual production on Africa and, by the transitive effect, African life.[36] For long enough, we have remained at a point where we are repeatedly reminded that we must protect (obviously at great cost) the imaginary intellectual contributions of Euro-American scholars who, we are assured, will one day certainly come up with all sorts of wondrous panaceas for the ‘African condition’. We are to protect their authority, their expertise, more than we are to safeguard the lives and dignities of existent, multiply silenced yet nonetheless present Africans from the harm that traipsing Western academics inflict in the name of evocative research. And the route to such heavenly harmony, we are again assured ad nauseum, is to ensure that we do not offend the sensibilities of these Global Northerners. The idea of a retracted article, therefore, rankles of censorship most foul, which must be guarded against with a zestful zealotry. But the marionetting of research subjects is something we must debate with great ‘scholarly objectivity’ like the social scientists we are supposed to be. We are in trouble. Of course, the pointed meditation I am presenting is this, what liberation from under the millstone of regressive scholarship is there to be found in an organisation that has long obfuscated pathways to clearer scholarship on Africa? What does an organisation that even refuses to be provincialised within the study of Africa—subjecting scholars on the continent to the insane syllabic gymnastics of sounding out ‘African Studies Association of Africa’—have to offer forward-looking individuals intent on engaging seriously with the continent and its peoples? Even in the naming there is a politic of centrality, an insistence that they retain the vantage as everyone else occupies a margin demarcated by a hyphen or preposition. You must then pardon the puzzled look on the face of the kindly consular officer at the South African embassy when I rattled off the purpose of my visit to Cape Town, ‘I’m going to attend the African Studies Association of Africa Conference’. What an unwieldy sentence! And at its every utterance, we are to be reminded of our place. Are we to be mediated by an organisation and its affiliates who insist that platforming, and defending full-throated, work that has been called out for its ridiculousness and dangerousness is a watershed moment for African scholars to contribute to commentary? A platform haughtily incapable of any degree of self-reflection to understand the milieu it engenders for those upcoming in the discipline and others valiantly soldiering on despite such conditions. A platform unwilling—and thus unable—to undertake any of the serious radical steps needed to alleviate said conditions. One that calls peeping voyeurism ‘excellent’. Should we not be so wise as to understand that an association which has been at the centre, even instigator, of these so-called ‘crises’ can have no unique insights to offer on the work that lies before us? Come out of her, my people! Notes [1] Achebe, C., 2009, ‘Africa is People’ and ‘Africa’s Tarnished Name’, in Africa’s Tarnished Name, New York: Penguin Random House. See also, Markel, H., 2016, Dr. Albert Schweitzer, a renowned medical missionary with a complicated history, PBS, 14 January. https://www.pbs.org/newshour/health/dr-albert-schweitzer-a-renowned-medical-missionary-with-a-complicated-history. [2] The Holy Bible, Authorized King James Version. (2009). Zondervan. Matt. 10:8. [3] Markel, Dr. Albert Schweitzer, a renowned medical missionary with a complicated history; Harris, R., 2016, Schweitzer and Africa, The Historical Journal, Vol. 59, No. 4, pp: 1107–1132. [4] Reuters, 1965, Albert Schweitzer, 90, Dies at His Hospital, New York Times Archive, 6 September. https://archive.nytimes.com/www.nytimes.com/learning/general/onthisday/bday/0114.html [5] Achebe, Africa’s Tarnished Name; See also, Marshall, K., 2011, Pilgrimage to Albert Schweitzer's Lambarene, Berkley Centre for Religion, Peace, and World Affairs, 5 September. https://berkleycenter.georgetown.edu/posts/pilgrimage-to-albert-schweitzer-s-lambarene and Wong, L. M., 2013, Albert Schweitzer Hospital celebrates its Centennial. Lisa M. Wong M.D, 25 July. http://www.drlisamwong.com/blog/albert-schweitzer-hospital-celebrates-its-centennial [6] This essay can itself be seen as patterned after Odugbemi, T., Orapeleng, R. and wa Kamonji, W, 2021, Searching For Africa In African Studies: An Open Letter To Teachers Of Africa. Human Rights Pulse, 11 June. https://www.humanrightspulse.com/mastercontentblog/searching-for-africa-in-african-studies-an-open-letter-to-teachers-of-africa; a similar form of writing is seen in the entirety of Africa Today 44, No. 2, April-June 1997; see also wa Ngũgĩ, M., 2021, White Privilege in African Studies: When You Are Done, Please Call Us, brittle paper, 28 January. https://brittlepaper.com/2021/01/white-privilege-in-african-studies-when-you-are-done-please-call-us/. [7] Reference to the white supremacist project in African Studies includes scholars, both Black and white, committed to the project; what wa Ngũgĩ calls “intellectual black face” in White Privilege in African Studies. The terms ‘Euro-American’, ‘white’, ‘Global North’ and ‘Western’ shall be used interchangeably. [8] Chan, S., 2013, ‘The Middle Kingdom and the Dark Continent: An essay on China, Africa and many fault lines’, in Chan, S., ed., The Morality of China in Africa: The Middle Kingdom and the Dark Continent, London and New York: Zed Books, pp. 3–43. [9] The Chronicle of Higher Education, 2022, Open Letter Against Harvard’s Treatment of John Comaroff, Chronicle, 3 February. https://www.chronicle.com/blogs/letters/open-letter-against-harvards-treatment-of-john-comaroff Accessed 1 June 2022. [10] The Harvard Crimson, 2022. Open Letter from Concerned Faculty: 38 Harvard Faculty Sign Open Letter Questioning Results of Misconduct Investigations into Prof. John Comaroff, The Harvard Crimson, 4 February. https://www.thecrimson.com/article/2022/2/4/comaroff-sanctions-open-letter/ Accessed 1 June 2022. [11] The Harvard Crimson, 2022. Czerwienski et al. v. Harvard, The Harvard Crimson, 8 February. https://www.thecrimson.com/PDF/2022/2/9/Czerwienski-et-al-v-harvard-filing/ Accessed 1 June 2022. [12] Harris, J. E. and Zeghidour, S., 1993, Africa and its diaspora since 1935, in Mazrui, A. A. and Wondji, C. eds, General History of Africa VIII: Africa Since 1935, Oxford: Heinemann, Paris: UNESCO, and Berkeley, CA: University of California Press, pp. 705–723; Howard University Center for African Studies, 2021, Re-Shaping a New US-Africa Policy and the Role of HBCUs. Center for African Studies, 20 February. https://cfas.howard.edu/articles/recording-symposium-re-shaping-new-us-africa-policy-and-role-hbcus; See also, Johnson, K., 2020, The Howard School of International Affairs, in Tella, O. and Motala, S., eds, From Ivory Towers to Ebony Towers: Transforming Humanities Curricula in South Africa, Africa and African-American Studies, Johannesburg: Jacana Media and Vitalis, R., 2015, White World Order, Black Power Politics: The Birth of American International Relations. Ithaca, NY and London: Cornell University Press, 2015. [13] Mboya, T., 1963, Freedom and After. Boston, MA and Toronto: Little, Brown and Company. [14] Dudziak, M. L., 2008, Exporting American Dreams: Thurgood Marshall's African Journey. Princeton, NJ and Oxford: Princeton University Press. [15]University of Minnesota, 2022, African History, accessed 1 June 2022. https://cla.umn.edu/history/graduate/areas-study. [16]Howard University Center for African Studies, 2022, African Languages. 2 June. https://cfas.howard.edu/. [17] wa Thiong'o, N., 1982, Decolonising the Mind: The Politics of Language in African Literature. Nairobi: East African Educational Publishers, p. 22. [18] Achebe, C., 2019, Impediments to Dialogue Between North and South, in Achebe, C., Hopes and Impediments, New York: Penguin Books, pp: 21-29. [19] Reuters, Albert Schweitzer, 90, Dies at His Hospital [20] Harris, Schweitzer and Africa, 1108. [21] Césaire, A., 1955, Discourse on Colonialism. Translated by Joan Pinkham. New York: Monthly Review Press, pp. 54–55. [22] Pronczuk, M. and Ryckewaert, K., 2022, A Racist Researcher, Exposed by a Mass Shooting, New York Times, 9 June. https://www.nytimes.com/2022/06/09/world/europe/michael-woodley-buffalo-shooting.html Accessed 13 June 2022. [23] Otaño-Gracia, N., 2022, A Critical Subjective Analysis of Objectivity. The H-Net Book Channel, 1 June 2022. https://networks.h-net.org/node/1883/discussions/10333626/critical-subjective-analysis-objectivity [24]Levy, A., 2020, A Missionary on Trial, The New Yorker, 6 April. https://www.newyorker.com/magazine/2020/04/13/a-missionary-on-trial; Starkey, J., 2021, SAFARI FIRE: Bungling British troops spark 10,000-acre wildfire on a nature reserve in Kenya home to elephants and lions. The Sun, 25 March. https://www.thesun.co.uk/news/14459767/british-troops-spark-10000-acre-wildfire-reserve-kenya/ (accessed 12 June 2022). [25] Editors of the African Studies Review, 2022, A Statement from the Editors of the African Studies Review, edited by Benjamin N. Lawrance et al., African Studies Review, 31 May. <a href="https://www.facebook.com/AfricanStudiesReview/posts/2684287641703042?__cft__%5b0%5d=AZVzvGm6Cxil4PaHq6tA5zVpolOzjKUJBfRSEp4GDHUoS61zmCMnOevrbqq8URRE6M0KnR9L7Ri14ujtvOLU3vHvkf17HrB_wb5sufJ22lOAuuaXb6rXDUCVysQyOQU36wFmyt0AuWshLyTNfdQxbpp3oHJKC4huOLKOXCdfq0hzych">https://www.facebook.com/AfricanStudiesReview/posts/2684287641703042?__cft__[0]=AZVzvGm6Cxil4PaHq6tA5zVpolOzjKUJBfRSEp4GDHUoS61zmCMnOevrbqq8URRE6M0KnR9L7Ri14ujtvOLU3vHvkf17HrB_wb5sufJ22lOAuuaXb6rXDUCVysQyOQU36wFmyt0AuWshLyTNfdQxbpp3oHJKC4huOLKOXCdfq0hzych (accessed 12 June 2022). [26]Burke, T., 2022, Academia: Retract or Attack? 19 May. https://timothyburke.substack.com/p/academia-retract-or-attack?s=r Accessed 1 June 2022. [27] See Sarah Shulist’s incisive reflection, On What Was Really Lost in the Fire, Anthropology As… 12 September. https://anthropologyas.wordpress.com/2018/09/12/on-what-was-really-lost-in-the-fire/ (accessed 6 July 2022). [28] Lawrance, B., Structural Racism, Whiteness, and the African Studies Review, African Studies Review, Vol. 63, No. 3, pp. 443–448. [29] Mohammed,W. et al., 2022, Open Letter to African Studies Review Journal Editorial Board: Call for Retraction of Article ‘African Studies Keyword: Autoethnography’, 16 May. https://docs.google.com/forms/d/e/1FAIpQLSdKo9OgNuU0DcYMBRbuTvv2wu-sJE3StYIIaFuclGJiDevx8g/viewform (accessed 10 June 2022). [30] wa Ngũgĩ, White Privilege in African Studies. [31]Flaherty, C., 2022, Retract or Attack? Inside Higher Ed. 24 May. https://www.insidehighered.com/news/2022/05/24/black-scholars-demand-retraction-autoethnography-article [32] Editors of the African Studies Review, A Statement from the Editors of the African Studies Review. [33] Mara, K. and Thompson, K., 2022, African Studies Keyword: Autoethnography, African Studies Review, Vol. 65, No. 2, pp. 372–398. doi:10.1017/asr.2022.58. pp. 375-376. [34] Ibid., pp. 372, 374, 378. [35] Achebe, C., 2005. ‘Colonialist Criticism.’ In Debating the Canon: A Reader from Addison to Nafisi, edited by Lee Morrissey, New York: Palgrave Macmillan, 73-85. p. 75. [36] Editors of the African Studies Review, A Statement from the Editors of the African Studies Review.